2021
DOI: 10.3390/microorganisms9122443
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NDM-1-Producing Carbapenemase in Proteus mirabilis among Broilers in China

Abstract: Carbapenem-resistant pathogens mediated by metallo-beta-lactamases (MBLs) have spread worldwide, where NDM-1 is a typical and key MBL. Here, we firstly discussed the distribution characterization of NDM-1, which produces multidrug-resistant Proteus mirabilis among broilers in China. From January to April 2019, 40 (18.1%, 40/221) blaNDM-1-carrying P. mirabilis strains were recovered from commercial broilers in slaughterhouse B in China. All the isolates were resistant to imipenem, meropenem and other β-lactams.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…In this study, the strains detected drug resistance genes containing most commonly used antimicrobial drugs, and the resistance phenotype showed highly resistance, which is consistent with the results of recent studies [ 27 – 29 ], which indicates that the resistance has been increasing in recent years. Moreover, a comparison of the bacterium’s resistance phenotype and genotype reveals a correlation between most drug resistances and the carried resistance genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the strains detected drug resistance genes containing most commonly used antimicrobial drugs, and the resistance phenotype showed highly resistance, which is consistent with the results of recent studies [ 27 – 29 ], which indicates that the resistance has been increasing in recent years. Moreover, a comparison of the bacterium’s resistance phenotype and genotype reveals a correlation between most drug resistances and the carried resistance genes.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we propose that the composite integron containing bla NDM−1 gene may have been integrated into the ICE (MDR region 2) transposon through IS sequences, subsequently transposing into the chromosome. This mode of transfer was previously observed in Proteus mirabilis isolated from livestock and food sources, where the chromosome-encoded bla NDM−1 gene was reported [ 2 , 27 , 29 ]. However, to our knowledge, this phenomenon is not common in CR-PMI strain isolated from human specimens.…”
Section: Discussionsupporting
confidence: 73%
“…The authors identified blaNDM in 21.8% of the E. coli isolates, 7.4% on K. pneumoniae while 3.9% in E. cloacae, with respect to different variants of blaNDM−5, blaNDM−9, blaNDM−1, and blaNDM−7. P. mirabilis with blaNDM, blaOXA−1, blaOXA−10 genes were isolated from chicken in their slaughter houses and chicken farms according to the study of (32). In addition, (33) also reported blaNDM-1 in isolates P. mirabilis in broiler chickens.…”
Section: Resultsmentioning
confidence: 99%
“…An important factor of bacterial resistance to antibiotics is bacteria's tendency to carry resistance-related genes ( Song et al., 2020 ; Liu et al., 2021b ; Wang et al., 2021a ; Liu et al., 2023 ). In past studies, the bla NDM gene has often been observed in poultry and poultry environments ( Hamza et al, 2016 ; Zhu et al, 2021 ), while other resistance-related genes, including bla KPC , bla IMP , and bla VIM-2 , have also appeared in carbapenem-resistant Gram-negative bacteria ( Bocharova et al, 2020 ; Algammal et al, 2021 ; Elmonir et al., 2021 ). In our study, all CRE strains carried genes encoding carbapenemases, and we observed detection rates of 91.7% (11/12) for bla NDM and 58.3% (7/12) for bla OXA .…”
Section: Discussionmentioning
confidence: 99%